ENVIRONMENTAL MANAGEMENT ACCOUNTING DI UNIVERSITAS: EVALUASI KESIAPAN IMPLEMENTASI EMA DALAM KONSUMSI KERTAS, LISTRIK DAN AIR - Bella Suhartono; Dianne Frisko (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The environmental damage has become popular issue to be concerned by society, government and business industries sectors, recently. Some studies found that most pollutions contributed by industrial sectors, therefore many tools have been applied by companies to minimize the waste. However, not for profit organization, government and society should also be responsible for the occurrence of environmental damage for their miss-consumption on fuel, paper, electricity, water, etc. University as academic institution consumes some resources mostly on paper and electricity, to support their daily learning and administration activities. In managing the resources consumption and minimising the waste, university may also apply environmental management accounting (EMA), which have been implemented at most industrial sectors. This study aims to determine the level of readiness of implementation of EMA on academic institution which most deal with resources such as paper, water and electricity. The research object of this case study is Faculty Ebiz in Surabaya, focusing on the way they consume and manage the use of paper, electricity, and water. As a qualitative research, the study uses some methods to collect data, which consists of deep interviews with some keypersons, documents analysis on the policy and data of resources’ consumption level, and observation some activities on location as non-participant observer. The results reveal that Faculty Ebiz has not been fully implemented EMA concept in the way of paper, electricity, and water consumptions. This case study determine the willingness of green commitment, and some particular activities from the civitas- academica should be supported by physical and technical policy to ensure the effectiveness of EMA’s implementation.